Louis Adamic, a Slovene, an American, an observer, a fighter, a 'poet' - Žitnik Serafin, Janja (Dve domovini, 1998)
In the paper, the author tries to present Louis Adamic's many-sided personality, regarding not only his relation to the prevailing value systems of his two homelands but also his relation to the major three roles in which he appeared: as a sensitive observer of the society and the individual, a public fighter for a better society, and a subtile conveyor of human feelings, predicaments and expectations.
Keywords: Adamič, Louis, 1898-1951; ameriški Slovenci; slovenski izseljenci; United States of America; ZDA